Multiple Equilibria and Minimum Wages in Labor Markets with Informational Frictions and Heterogeneous Production Technologies - Gerard J. van den Berg (Tinbergen Institute, 1999)
It is often argued that a mandatory minimum wage is binding only if the wage density displays a spike at it. In this paper we analyze a model with wage setting, search frictions, and heterogeneous production technologies, in which imposition of a minimum wage affects wages even though, after imposition, the lowest wage in the market exceeds the minimum wage, and subsequent abolition of the minimum wage does not affect wages. The model has multiple equilibria as a result of the fact that the reservation wage of the unemployed and the lowest production technology in use affect each other. Under certain conditions, imposition of a minimum wage improves social welfare.
Keywords: 330; wages; productivity; job search; unemployment; imperfect information; Arbeitsmarkt; Lohnstruktur; Mindestlohn; Arbeitsuche; Gleichgewichtstheorie; Theorie